2015
DOI: 10.1002/sca.21232
|View full text |Cite
|
Sign up to set email alerts
|

Useful surface parameters for biomaterial discrimination

Abstract: Topographical features of biomaterials' surfaces are determinant when addressing their application site. Unfortunately up to date there has not been an agreement regarding which surface parameters are more representative in discriminating between materials. Discs (n = 16) of different currently used materials for implant prostheses fabrication, such as cast cobalt-chrome, direct laser metal soldered (DLMS) cobalt-chrome, titanium grade V, zirconia (Y-TZP), E-glass fiber-reinforced composite and polyetheretherk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…The high positive correlations between most of the roughness parameters and their overlapping confidence intervals explain why none of the parameters were significantly more suitable to predict the initial microbial adhesion than R a . The low discriminatory powers of the surface roughness parameters in the present study are opposed to a study that stated that S a and S z are appropriate parameters to discriminate between the polished surfaces of dental materials [20]. If the profile and surface roughness parameters of a material show more discriminatory powers than in the present study, parameters other than R a will be associated significantly more with initial microbial adhesion.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The high positive correlations between most of the roughness parameters and their overlapping confidence intervals explain why none of the parameters were significantly more suitable to predict the initial microbial adhesion than R a . The low discriminatory powers of the surface roughness parameters in the present study are opposed to a study that stated that S a and S z are appropriate parameters to discriminate between the polished surfaces of dental materials [20]. If the profile and surface roughness parameters of a material show more discriminatory powers than in the present study, parameters other than R a will be associated significantly more with initial microbial adhesion.…”
Section: Discussioncontrasting
confidence: 99%
“…Generally, a high positive correlation between the roughness parameters indicates redundancy and low discriminatory powers to characterize surfaces of biomaterials [20]. In the present study, all of the parameters that describe the heights or valleys showed a high positive correlation, except for the roughness parameters that describe distinctive qualities such as the kurtosis (R ku and S ku ), skewness (R sk and S sk ), or material component (R mr ) of a profile or a surface.…”
Section: Discussionsupporting
confidence: 40%
See 3 more Smart Citations